Gibbsian Description of Gaussian Random Fields - Khachatryan, Linda (Armenian Journal of Mathematics, 2025)
This paper provides the solution to the problem of Gibbsian description of Gaussian random fields based on the Gibbs scheme currently being developed in the theory of lattice random fields.
Keywords: Gibbs Random Field; Gaussian Random Field; Conditional Densities; Gibbs Form of Conditional Densities; Transition Energy; Hamiltonian; Markov Random Field